Web-based control of a digital pendulum system - Chasqueira, Hugo (2019)
This paper proposes a Web-based architecture to monitor and experiment a Digital Pendulum Control System from a remote place. The Digital Pendulum Control System is an interesting educational tool considered ideal for both laboratory and project work, and a typical case of a computer control application.